Penerapan Sosialisasi Digital Marketing Dan Pembuatan Marketplac Sebagai Upaya Peningkatan Penjualan Di Kelurahan Pakunden Dan Kelurahan Turi Kecamatan Sukorejo - Fani Khoirotunnisa; Izah Bana Murtazah; Sheni Nahla Syifani; Moch. Syahrir Sauki (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Technology has developed rapidly in the age of scientific progress. This is unavoidable because technology can provide positive benefits for developing product innovations. With the existence of technology, humans can use it as access to search for extensive information via the internet. Socialization of Digital Marketing and Creating a Marketplace for MSME Players